Income effects of alternative trade policy adjustments on Philippine rural households: a general equilibrium analysis - Bautista, Romeo M.; Thomas, Marcelle (International Food Policy Research Institute, 1997)
Three types of trade policy adjustments to deal with an unsustainable current account deficit are examined in this paper for their economywide income and equity effects, based on the results of simulation experiments using a CGE model of the Philippine economy. Gross domestic product (GDP) expectably decreases with import rationing and less markedly, with the imposition of a general import surtax; by contrast, adjustment through the reduction of tariffs leads to a larger GDP. The latter result, however, is counterbalanced by a substantial loss in government income. With respect to the distribution of income gains (and losses), the additional market distortions and rent-seeking that accompany the implementation of import rationing heavily discriminate in favor of Metro Manila households, whose average income is the highest among the five household groups distinguished in the model. Moving to a general import surtax represents an improvement in that non-Metro Manila households are penalized less. However, these first two policy options are deemed inferior to tariff liberalization--which yields larger income benefits to small-farm and other rural households relative to the more affluent Metro Manila, other urban, and large-farm households.